STUDY OF MORPHOLOGY AND SHORELINE CHANGES OF BALONGAN WATERS - SETIABUDI SRIRAHARJO - NIM: 25015311, YUWANA
The coastal region of Balongan is an ecosystem that is sensitive to environmental changes. Where the shoreline changes due to the erosion that greatly affect. Another damage problem between abrasion, high tidal threats, and no vegetation to protect coastal areas. Therefore, further and in-depth study on the phenomena of coastline change is needed. In reviewing shoreline changes is very easy when using satellite imagery to review those changes. Because we can immediately see what kind of damage is happening on the beach. According to satellite imagery data compiled for 16 years shows shoreline changes of 20 meters or 1.25 meters per year. The shoreline changes are determined by the dynamics occurring in the coastal waters. Waves, ups and downs, ocean currents, and sedimentation affect the change of coastline. Coastal location that is relatively open to the influence of the direction of the sea affects the coast. Sedimentary characters also have a role in the dynamics of the coastline, because the sediment will form the mass of the land in an area. In addition, the human factor can lead to changes in coastline, because the infrastructure built on the area will directly affect the coastal morphology. To review the shoreline changes in a region can use various methods one of which is to use numerical modeling. In the model to be used to note the input factors so that the expected results can be appropriate. Because in reviewing the shoreline changes it takes long-term hydro-oceanographic data, therefore it will use global data. The data and results obtained from the model will be validated and verified with field data. So that will be obtained how the pattern of coastline changes in Balongan. Based on the analysis result, it is found that the roughness value of manning used as calibration in the model shows that the roughness value gives the lowest error value after it is verified with the tide and current data of the field measurement. The result of wave transformation in August to November 2016 from the east, is relatively moving perpendicular to the coast, while in December 2016 until March 2017 the wave from the East direction of refraction when approaching the coast. The result of sediment transport modeling shows that, in the area near the harbor there is a relatively bigger erosion than the coastal area. The erosion is related to the velocity around the site, where the diameter d50 around the site of 0.1 mm can be explained by the minimum speed of 0.015 m / s. Based on the calculation of the basic changes compared to field measurement data, it shows the similarity of results. Changes in shoreline due to erosion that occurred that the coast experienced a setback of 1 meter to 2.5 meters per year. The results of coastline changes have been compared with satellite images and show relatively similar results. Shoreline changes for 10 years from 2016 to 2026 show deterioration if no protection measures are taken. Ongoing erosion will damage the infrastructure located around the coast.